Numerical study of the packing density of fine powders by means of the Discrete Element Method - Blümel, Christina; Ribeiro Parteli, Eric Josef; Schmidt, Jochen; Wirth, Karl Ernst; Peukert, Wolfgang; Pöschel, Thorsten (85th Annual Meeting of the International Association of Applied Mathematics and Mechanics – GAMM 2014, 2014)
Numerical simulations by means of the Discrete Element Method (DEM) can provide a helpful tool in the investigation of the packing behavior of powders. In this type of numerical simulations, the Newton’s equations of motion for every single particle in the system are solved by taking into account all forces and torques acting on it, both due to external fields and due to interactions with other particles in the system